Mining before COVID-19: Local development based on a new normality - Franco Bojórquez, Edna María (Posgrados de la División de Ciencias Económica Administrativas, 2022)
With the arrival of SARS-CoV-2 and its variants, local economic development has been modified by virtue of the necessary measures to minimize the risk of contracting the Covid-19 disease. Among the economic activities directly affected by this disease is mining, which, although it is responsible for providing minerals as raw material for other sectors, was not mentioned within the essential activities by the Official Gazette of the Federation (with the exception of coal mines); affecting the local development that the mining companies provide to their community and in deterioration of the entity in which they are located. The objective of this article is to analyze the effects that the Covid-19 pandemic has had on the mining industry and how the new normality applied to the world population establishes new parameters to carry out the production of minerals, demonstrating the ability to adapt that has mining as an industry, in order to continue its activities. The methodology is of a mixed nature since it collects a vision obtained from the observation and application of questionnaires to the various mining actors in the state of Sonora, as well as statistical data that link mining activity and Covid-19. The results show that the transition from non-essential to essential activity implies a recognition of the fact that mining is raw material and input to develop means that allow, in this case, to combat Covid-19. In conclusion, despite criticism of mining in the sense that it is a polluting activity, it is clear that it has a positive side as a productive force for development.